(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the ways and methods of organizing interactive games using artificial intelligence tools in primary school native language lessons. The opinions of scientists on how to use artificial intelligence tools in native language lessons are presented. It is shown that the ability to organize a traditional lesson and an interactive lesson depends on the pedagogical skills of the teacher, and how effective it is for students is analyzed.